Remotely Sensing Digital Methods For Dust Storms Monitoring In Iraq - Hassan, Mustafa (Iraqi Journal of Science, 2024)
In this research, attempt to overcome and quantities the problem of the large number of frequency of dust storms and the areas that generated and then identifying these areas in order to be held by the agricultural areas, as has been the adoption of many of the techniques and methods of processing image in remote sensing and geographic information systems and linking them together to identify those areas in Iraq or the neighbors, especially the northern and north-west wind of the fact that Iraq is in the northern and north - western most days of the year. Research has included the use of images from the satellite (MODIS) with quality (Aqua) and (Terra) with the assembly of the amount of dust, these storms, it was determining the values of size and density of the dust and the amount (> 10μm) and (ρ = 1.58 mg/m3) respectively, note that this dust has collected from the University of Baghdad during a sandstorm brief summary on July 2010, because this month is the most higher month temperature in the year and it was about 50 thousand ton of dust in each dust storm. To extract all the results and information that obtained from the operations account amounts that the soil is expected calculated annually for these storms and to determine the threshold line density of this dust in the air. Finally, developing a system to monitor these storms, depending on the capacity of scientific instruments of modern used in the countries of the world and its establishment in Iraq.